Studies and Essays: Censorship and Art - Galsworthy, John, 1867-1933 (Salt Lake City, UT : Project Gutenberg, 2004)
"Studies and Essays: Censorship and Art" by John Galsworthy is a collection of essays written in the early 20th century that explores the intricate relationship between censorship and artistic expression. This thought-provoking work delves into the necessity and implications of censorship in various realms such as literature, drama, art, religion, and politics. Galsworthy argues that while censorship may be perceived as a protective measure for societal comfort, it raises essential questions about freedom, creativity, and the responsibilities attached to artistic endeavors. In the essays, Galsworthy critiques the existing censorship system that primarily targets plays and urges for similar restrictions to be applied across literature, art, and science to safeguard public sensibilities. He posits that the censorship of art forms is crucial to maintain societal decorum, especially considering the mixed audiences in public spaces. Furthermore, he reflects on the nature of art itself, proposing a definition that emphasizes its ability to evoke impersonal emotion and create a harmonious connection between individuals and universal experiences. Through his contemplative style, Galsworthy navigates complex philosophical ideas, questioning the boundaries of artistic freedom and the role of the audience in interpreting art's significance. (This is an automatically generated summary.)
About censorship $1 (BVague thoughts on art.s
Release date is 2004-09-25
Produced by David Widger
Keywords: Art; Art -- Censorship; Art -- Philosophy